ChemInform Abstract: Total Synthesis of Proposed Cephalosporolides H and I. Issue 39 (September 2015) - Li, Jinshan; Zhao, Chuanfang; Liu, Jun; Du, Yuguo
Abstract Total synthesis of the reported title compounds (I) and (II) suggests an S‐configuration at the spiro‐C‐atom instead of the reported R‐configuration.